2012
DOI: 10.1002/dvdy.23829
|View full text |Cite
|
Sign up to set email alerts
|

Tol2 gene trap integrations in the zebrafish amyloid precursor protein genes appa and aplp2 reveal accumulation of secreted APP at the embryonic veins

Abstract: Background-The single spanning transmembrane amyloid precursor protein (APP) and its proteolytic product, amyloid-beta (Aβ) peptide, have been intensely studied due to their role in the pathogenesis of Alzheimer's disease. However, the biological role of the secreted ectodomain of APP, which is also generated by proteolytic cleavage, is less well understood. Here, we report Tol2 red fluorescent protein (RFP) transposon gene trap integrations in the zebrafish amyloid precursor protein a (appa) and amyloid precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A␤PP has also been shown to have a very wide range of cellular functions. A␤PP influences Fe ion homeostasis via its interaction with Ferroportin (SLC40A1, [125]) and A␤PP affects embryo development, including vascular development, possibly via secretion of its extracellular/luminal domain [126,127] and A␤ [128]. A␤PP also influences the rate of protein synthesis [129], neurite outgrowth [130], and axonal pruning [131] as well as LPSmediated innate immune responses [132].…”
Section: What Then Of A␤pp A␤ and The A␤ 42 /A␤ 40 Ratio?mentioning
confidence: 99%
“…A␤PP has also been shown to have a very wide range of cellular functions. A␤PP influences Fe ion homeostasis via its interaction with Ferroportin (SLC40A1, [125]) and A␤PP affects embryo development, including vascular development, possibly via secretion of its extracellular/luminal domain [126,127] and A␤ [128]. A␤PP also influences the rate of protein synthesis [129], neurite outgrowth [130], and axonal pruning [131] as well as LPSmediated innate immune responses [132].…”
Section: What Then Of A␤pp A␤ and The A␤ 42 /A␤ 40 Ratio?mentioning
confidence: 99%
“…As a vertebrate model, zebrafish has been used to reveal particular characteristics of the various genes implicated in AD, which have been difficult to observe in other animal models. 36,37 A mutant zebrafish lacking PSEN1 has been used to study the histaminergic neural system of the brain, which is essential in mediating the cognitive functions affected in AD. Analysis of histamine neuron numbers in the PSEN1 −/− zebrafish brain revealed that PSEN1 is a regulator of histaminergic neuronal development.…”
Section: Natural Ad Modelsmentioning
confidence: 99%